Pendampingan Pemasaran Digital Kepada Pelaku UMKM Abon Ikan Patin di Desa Jatimekar Kecamatan Jatiluhur - Alpiani, Yuli; Zulfikal, Muhamad; Oktapianti, Mila Sari (STIE Syariah Indonesia Purwakarta, 2022)
In order to increase the income of fishermen, one of them is processing fish catches to be used as food ingredients, so that processing has added value for fishermen to meet their daily needs. After the fish was successfully made into shredded catfish, further problems arose related to the marketing of the shredded catfish product, especially during the Covid-19 pandemic, all community activities were limited. This marketing problem is often a major problem for MSME players who are not literate or keep abreast of technological developments, including the shredded catfish MSME actors who still do not understand the use of social media as an effective marketing medium in generating many profits. The aim of the PKM is to help increase the sales of MSME actors in Shredded catfish in Jatimekar Jatiluhur Village, Purwakarta. The method used in this PKM program uses socialization and mentoring methods. The results of this PKM technically have been successfully implemented. The shredded catfish MSME actors have experienced changes both in terms of understanding and in terms of marketing. Initially, the shredded catfish MSME actors were still unfamiliar with digital marketing, now they understand digital marketing, including stages by stages in digital marketing. In addition, the MSME actors of shredded catfish, which previously used traditional methods in marketing the shredded catfish product, are now starting to use several marketplaces and Websites, even though the Website is still affiliated with the village.